The Strategic Frameworks in Digital Marketing Communication for Educational Institutions: A Case Analysis of Universitas Islam Negeri in Indonesia - Saputra, Andika; Aras, Muhammad (ILTIZAM Journal of Shariah Economics Research, 2023)
In the ever evolving and highly competitive business landscape, the image of an organization, particularly in the realm of higher education, plays a pivotal role. This article proposes a strategic framework for digital marketing communication within educational institutions, with a case analysis drawn from Universitas Islam Negeri Sulthan Thaha Saifuddin Jambi. We delve into the significant impact of information technology and the internet, reshaping communication paradigms on a global scale. Emphasizing the critical importance of a university’s image in shaping societal perceptions and influencing educational choices, we explore the concept of brand image in the context of education. Detailing digital marketing strategies as a solution to enhance visibility, appeal, and the reputation of higher education institutions, this article elucidates how technological innovations and digital platforms serve as effective means for universities to connect with a broader audience, including prospective students, alumni, and potential partners. Through a case study analysis, we underscore the pivotal role of digital marketing in building and fortifying a positive image, as well as addressing potential reputation issues. The outcomes of this research provide strategic insights for universities to implement effective digital marketing communication, guiding them towards achieving their goals in this digital era.